Mycosporine-like amino acid and aromatic amino acid transcriptome response to UV and far-red light in the cyanobacterium Chlorogloeopsis fritschii PCC 6912 - Llewellyn, Carole A. (Sci Rep, 2020)
The “UV sunscreen” compounds, the mycosporine-like amino acids (MAAs) are widely reported in cyanobacteria and are known to be induced under ultra-violet (UV) light. However, the impact of far red (FR) light on MAA biosynthesis has not been studied. We report results from two experiments measuring transcriptional regulation of MAA and aromatic amino acid pathways in the filamentous cyanobacterium Chlorogloeopsis fritschii PCC 6912. The first experiment, comparing UV with white light, shows the expected upregulation of the characteristic MAA mys gene cluster. The second experiment, comparing FR with white light, shows that three genes of the four mys gene cluster encoding up to mycosporine-glycine are also upregulated under FR light. This is a new discovery. We observed corresponding increases in MAAs under FR light using HPLC analysis. The tryptophan pathway was upregulated under UV, with no change under FR. The tyrosine and phenylalanine pathways were unaltered under both conditions. However, nitrate ABC transporter genes were upregulated under UV and FR light indicating increased nitrogen requirement under both light conditions. The discovery that MAAs are upregulated under FR light supports MAAs playing a role in photon dissipation and thermoregulation with a possible role in contributing to Earth surface temperature regulation.